A comparative study of tension band wiring and encirclage in treating transverse fractures of patella - Mohapatra, Subrat; Das, Pulin Bihari; Krishnakumar, R. V.; Rath, Sibanarayan; Padhy, Rabindra N. (International Surgery Journal, 2017)
Background: The functional and radiological outcome of the union of transverse fractures of patella treated by tension band wiring (TBW) and encirclage wiring were compared according to WEST’s criteria. Methods: During three years, 44 patients with displaced transverse fracture patella were treated randomly either by TBW or encirclage with twenty-two patients in each group. Two patients in each group were lost to follow-up. Results: Results were compared based on the period of union, post-operative complications, early mobilization and recovery to pre-injury level. Fractures united at an average of 13.6 weeks with 8-12 and 10-14 weeks in TBW and the encirclage group, respectively. Results were excellent in 65%, good in 25% and poor in 10% cases in TBW group, as compared to the encirclage group with excellent in 50%, good in 30% and poor in 20% cases. In TBW group, 75% cases had a full range of motion (ROM), 15% had >120° of flexion and 10% had flexion between 90° and 120°, as compared to 50% full ROM, 30% >120° of flexion and 20% between 90° and120° flexion in the encirclage group. A case of migration of pin and another case of limitation of flexion by 25° were noticed. Conclusions: Patients treated with TBW had better results than the encirclage in the management of transverse fractures of the patella.